Kultywacja języka - starsze i nowsze koncepcje w ujęciu ekolingwistycznym = Language cultivation: older and newer concepts in ecolinguistic approach - Steciąg, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper is to present the ecolinguistic view on the problem of language cultivation in contemporary socio-cultural context. Language policy shaped by this perspective will seek to attain balance within the overall sociolinguistic ecosystem by encouraging tolerance for linguistic diversity and the cultivation of as many language varieties as possible.
Keywords: ekolingwistyka; kultywacja języka; zarządzanie językiem; higiena werbalna; ecolinguistics; language cultivation; language management; verbal hygiene